2019
DOI: 10.1002/jcb.28430
|View full text |Cite|
|
Sign up to set email alerts
|

Silencing of HAS2‐AS1 mediates PI3K/AKT signaling pathway to inhibit cell proliferation, migration, and invasion in glioma

Abstract: Hyaluronan synthase 2 (HAS2)-AS1 (natural antisense transcript of HAS2) functions as oncogenic long noncoding RNA (lncRNA) in oral squamous cell carcinoma, breast cancer, and osteosarcoma. The role of HAS2-AS1 in glioma remains unknown. In our research, HAS2-AS1 expression was elevated in glioma tissues compared with normal brain tissues. Moreover, high levels of HAS2-AS1 expression was observed in patients with glioma with high WHO grade (III-IV) or large tumor size (>4 cm). The survival analysis from The Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Recent studies have demonstrated the possible potential molecular pathways for SPHK1 and HAS2 in cancer progression, one of which is that SPHK1 induces lung cancer cell migration and paclitaxel resistance by modulating IGF-1-induced EMT [ 27 ]. HAS2 mediated hyaluronan production through Notch1 activation and liver fibrosis [ 28 , 29 ]. The GO and KEGG results showed that the coregulated genes mainly involved in cell invasion, cell adhesion, and positive regulation of angiogenesis by ECM-receptor interaction, focal adhesion, and PI3K-AKT signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated the possible potential molecular pathways for SPHK1 and HAS2 in cancer progression, one of which is that SPHK1 induces lung cancer cell migration and paclitaxel resistance by modulating IGF-1-induced EMT [ 27 ]. HAS2 mediated hyaluronan production through Notch1 activation and liver fibrosis [ 28 , 29 ]. The GO and KEGG results showed that the coregulated genes mainly involved in cell invasion, cell adhesion, and positive regulation of angiogenesis by ECM-receptor interaction, focal adhesion, and PI3K-AKT signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…HA degradation has been explored as a therapeutic target in several studies ( 68 , 76 , 77 , 117 , 221 , 222 ). Clinical trials have shown that treatment with HYAL as adjuvant chemotherapy improves drug biodistribution and particularly access to the tumor site, contributing to clinically relevant remissions in high-grade astrocytomas and to the efficacy of chemotherapy in pediatric brain tumors ( 223 , 224 , 225 ).…”
Section: Hyaluronan As a Therapeutic Target In Glioblastomamentioning
confidence: 99%
“…Multiple studies have reported that HAS2-AS1 is involved in the regulatory mechanism of ceRNA network and modulates the proliferation and migration of tumor cells [13,18]. Here, HAS2-AS1 was chosen for follow-up experiments.…”
Section: Silencing Has2-as1 Inhibits Glioma Cell Invasion and Migrationmentioning
confidence: 99%
“…Related studies have found that HAS2-AS1 is abnormally expressed in a variety of cancers, such as epithelial ovarian cancer [9], breast cancer [10], non-small cell lung cancer [11] and oral squamous cell cancer [12], and induces the development of cancers. Silencing of HAS2-AS1 mediates PI3K/Akt signaling pathway to inhibit cell proliferation, migration, and invasion of glioma [13]. However, the mechanism of the high expression of HAS2-AS1 in glioma is still unknown.…”
Section: Introductionmentioning
confidence: 99%